Preferensi Konsumen Dalam Memilih Bank BRI dan Bank BCA Di Manado Berdasarkan Kualitas Pelayanan - Tumbelaka, Andro; Kindangen, Paulus; Kalangi, Johnny A. F (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
The immediate objectives of this research study is to find out which criteria are the most influential in choosing a bank and to find out which bank is preferred by sustomers between BRI bank and BCA bank in Manado. Quantitative research was adapted as a method in this study and used a questionnaire as a flection of the method. The sample in this study were all customers of Bank BRI, and Bank BCA who had experience with the two banks. The questionnaire will be distributed using the purposive sampling method. The analytical method used in this study is the Analytical Hierarchy Process (AHP) where this method can rank criteria and produces weights for each evaluation criterion according to pairwise comparisons of decisions of decision makers of the criteria, so that researchers get a good picture of using the criteria.